Taking the mystery away from shared intentionality: The straightforward view and its empirical implications - Vincini, Stefano (Frontiers in Psychology, 2023)
Ordinary language in Western and non-Western cultures individuates shared mental states or experiences as unitary interpersonal events that belong to more than one individual. However, a default assumption in modern Western thought is that, in this regard, ordinary language is either illusory or merely metaphorical: a mental state or experience can belong to only one person. This assumption is called Cartesian eliminativism and is often taken to be foundational in psychology. It follows that any view that contradicts Cartesian eliminativism is a priori suspected of being “mysterious,” i.e., of being unable to hold up to scientific standards. This paper suggests that the very opposite may be the case. The straightforward view explains how individuals assemble and experience a shared mental state as a unitary whole whose components are distributed among the participants. The naturalistic advantages of such a view are brought to light by focusing on developmental science. Since it explains early shared emotions, goals, and attention by merely relying on domain-general, associative processes, the straightforward view is more parsimonious than current psychological theories. Indeed, it abandons the cumbersome postulates of (i) multi-level recursive mindreading and (ii) a special, conceptually elusive phenomenal quality. I outline the distinctive developmental predictions of the view and discuss how it accounts for the functions of shared mental states. As a reductionist, non-eliminativist approach, the straightforward view promises to be viable also for cognitive scientists who have so far worked within the Cartesian framework due to a lack of a rigorous and sufficiently developed alternative.